THE DEVELOPMENT OF EPISTEMOLOGICAL VIEWS IN MODERN WESTERN PHILOSOPHY (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. This article analyzes the formation and development of the theory of knowledge in Modern Western philosophy. The views of such thinkers as René Descartes, Francis Bacon, John Locke, Benedict Spinoza, and Gottfried Leibniz on human cognition, experience, reason, and truth are highlighted. In addition, the differences and significance of the philosophical trends of rationalism and empiricism are examined.